DNA alteration‐based classification of uveal melanoma gives better prognostic stratification than immune infiltration, which has a neutral effect in high‐risk group. (25th April 2019) - Narasimhaiah, Deepti; Legrand, Catherine; Damotte, Diane; Remark, Romain; Munda, Marco; De Potter, Patrick; Coulie, Pierre G.; Vikkula, Miikka; Godfraind, Catherine
Abstract: Background: In uveal melanomas, immune infiltration is a marker of poor prognosis. This work intended to decipher the biological characteristics of intra‐tumor immune population, compare it to other established biomarkers and to patients' outcome. Methods: Primary, untreated, and mainly large uveal melanomas with retinal detachment were analyzed using: transcriptomic profiling (n = 15), RT‐qPCR (n = 36), immunohistochemistry (n = 89), Multiplex Ligation‐dependent Probe Amplification (MLPA) for copy number alterations (CNA) analysis (n = 89), array‐CGH (n = 17), and survival statistics (n = 86). Results: Gene expression analysis divided uveal melanomas into two groups, according to the IFNγ/STAT1‐IRF1 pathway activation. Tumors with IFNγ‐signature had poorer prognosis and showed increased infiltration of CD8 + T lymphocytes and macrophages. Cox multivariate analyses of immune cell infiltration with MLPA data delineated better prognostic value for three prognostic groups (three‐tier stratification) than two (two‐tier stratification). CNA‐based model comprising monosomy 3, 8q amplification, and LZTS1 and NBL1 deletions emerged as the best predictor for disease‐free survival. It outperformed immune cell infiltration in receiver operating characteristic curves. The model that combined CNA and immune infiltration defined risk‐groups according to the number of DNA alterations. Immune cell infiltration was increased in the high‐risk group (73.7%), where it did not correlate with patient survival, while it was associated with poorer outcome in the intermediate risk‐group. Conclusions: High degree of immune cell infiltration occurs in a subset of uveal melanomas, is interferon‐gamma‐related, and associated with poor survival. It allows for two‐tier stratification, which is prognostically less efficient than a three‐tier one. The best prognostic stratification is by CNA model with three risk‐groups where immune cell infiltration impacts only some subgroups. Abstract : In uveal melanomas with high‐risk copy number alterations, immune infiltration has no impact on prognosis and is an epiphenomenon.